Lessons from the EU Accession for Agricultural Enterprises in the Visegrad Group Countries in the Light of CAP 2014 - Toro-Dunay, Anna; Gábriel-Tőzsér, Györgyi; Illés, Csaba; Vinogradov, Sergey (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2012)
The importance of evaluating different impacts of the EU accession has not decreased in the last decade. Some of the problems, such as the problems of competitiveness and effectiveness of the agricultural sector, or the delay in transformation of the payment scheme are still unsolved. The continuous learning process has not ended by the accession; not only institutions but also individuals shall observe and learn the changes of the agricultural policy, which of course means a heavy task for farmers, besides the management of their farming activities. This paper wishes to examine how the agricultural enterprises in Visegrad countries could utilize advantages of the EU accession and what kind of problems has arisen during the accession process. These questions became more actual in present days, as a draft of the new CAP reform was announced in October 2011. Thus, the readiness of farmers will have a great importance in the future. Without knowing the new system, the opportunities cannot be utilized, and without taking these advantages we cannot speak about a competitive and effective agricultural sector.